Innate immune response against vector-borne bunyavirus infection and viral countermeasures - Li, Minghua (Frontiers in Cellular and Infection Microbiology, 2024)
Bunyaviruses are a large group of important viral pathogens that cause significant diseases in humans and animals worldwide. Bunyaviruses are enveloped, singlestranded, negative-sense RNA viruses that infect a wide range of hosts. Upon entry into host cells, the components of viruses are recognized by host innate immune system, leading to the activation of downstream signaling cascades to induce interferons (IFNs) and other proinflammatory cytokines. IFNs bind to their receptors and upregulate the expression of hundreds of interferon-stimulated genes (ISGs). Many ISGs have antiviral activities and confer an antiviral state to host cells. For efficient replication and spread, viruses have evolved different strategies to antagonize IFN-mediated restriction. Here, we discuss recent advances in our understanding of the interactions between bunyaviruses and host innate immune response.